Leisure time and its impact on the child - Ahmed, Raghad; Qanbar, Firas (Al-Adab Journal, 2023)
It is certain that leisure time is linked to the nature of permanent construction in society، the level of civilized development، the degree of complexity of social life، and the productive and technological system. Participation is not، in their opinion، a way to spend leisure time. It all means an organized way of life in society، which must be taught and followed by children. The aim of this research is to know the benefits and harms of leisure time and its positive and negative effects on the child. Several results emerged from this study، the most important of which are:1- Parents follow up on their children and make use of their free time.2- The economic factor of the family has an impact on children's leisure time utilization.3- There are statistically significant differences between the child's age and the parents' consideration of age differences with regard to the division of leisure time for their children.